2015
DOI: 10.1016/j.marpolbul.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Microbial water quality and sedimentary faecal sterols as markers of sewage contamination in Kuwait

Abstract: Microbial water quality and concentrations of faecal sterols in sediment have been used to assess the degree of sewage contamination in Kuwait's marine environment. A review of microbial (faecal coliform, faecal streptococci and Escherichia coli) water quality data identified temporal and spatial sources of pollution around the coastline. Results indicated that bacterial counts regularly breach regional water quality guidelines. Sediments collected from a total of 29 sites contained detectable levels of copros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 23 publications
1
43
0
2
Order By: Relevance
“…Kuwait experiences a wide range of environmental conditions, with temperature and salinity being at the extremes of known conditions (Riegl, 2003;Devlin et al, 2015b), atmospheric fallouts carried by North Western dust storms and particulate matter derived by river transport from the Shatt Al-Arab and increasing coastal pollution (Sheppard, 1993;Sheppard et al, 2012;Al-Sarawi et al, 2015). Coastal water quality issues are significant for Kuwait, with many sewage outfalls discharging directly into the marine environment that are either not properly treated or illegally bypassing the sewage treatment facilities (Lyons et al, 2015;Saeed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwait experiences a wide range of environmental conditions, with temperature and salinity being at the extremes of known conditions (Riegl, 2003;Devlin et al, 2015b), atmospheric fallouts carried by North Western dust storms and particulate matter derived by river transport from the Shatt Al-Arab and increasing coastal pollution (Sheppard, 1993;Sheppard et al, 2012;Al-Sarawi et al, 2015). Coastal water quality issues are significant for Kuwait, with many sewage outfalls discharging directly into the marine environment that are either not properly treated or illegally bypassing the sewage treatment facilities (Lyons et al, 2015;Saeed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of eutrophication and coastal sewage issues have been identified in many Gulf countries including long-term coastal pollution in Kuwait (Devlin et al, 2015a;Lyons et al, 2015;Smith et al, 2015), changes in macrobenthic community structure in Bahrain (Naser, 2011), eutrophication related blooms in the Red Sea (Mohamed and Mesaad, 2007), eutrophication impacts on coral reefs in Oman (Al-Jufaili et al, 1999) and longterm degradation from coastal pollution reported across the Gulf marine systems (Price et al, 1993;Sheppard, 1995Sheppard, , 2016Subba Rao and Al-Yamani, 2000;Sheppard et al, 2010Sheppard et al, , 2012. The recent observed global increase in severity and frequency of harmful algal blooms (HAB) events has also been linked to eutrophication (Gilbert et al, 2002;Gilbert, 2006;Heisler et al, 2008) although not all HAB events can be directly linked to anthropogenic influences.…”
Section: Introductionmentioning
confidence: 99%
“…as a result, 2,300 m 3 of sewage per hour was flowing into the gulf of gdansk. Similarly, due to a malfunction at the Mishref Pumping Station, massive quantities of raw sewage was being discharged directly into the gulf for the period of 3 years (2009-2012); this-led to bacteriological contamination of a coastal section of about 20 km [8]. Other studies, however, suggest that it is heavy rainfall or floods which contribute to a higher number of faecal bacteria in coastal seawaters.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the outflow of rainwater and floods also contributes to the biological as well as chemical contamination of the coastal seawaters [5][6][7]. an example of this type of event was a serious malfunction at the Mishref Pumping Station, which resulted in sewage discharge and an increase in the number of coliform bacteria, Escherichia coli and faecal streptococci in the waters of the gulf of Kuwait [8]. Potentially pathogenic bacteria, mould fungi and enteroviruses are a significant factor influencing bathing water quality.…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com a forma de utilização da água devemos considerar as propriedades de qualidade definidas pelos parâmetros e padrões de potabilidade descritos por lei e normatizações sanitárias (OCHOO; VALCOUR; SARKAR, 2017). A averiguação desses parâmetros e padrões reforça a garantia do uso ou consumo da água para que não apresente riscos à saúde humana (LYONS et al, 2015).…”
Section: Introductionunclassified